Effects of diet and exercise in reversing Type 2 Diabetes Mellitus: a systematic review - Ashar, Nurul Nadiah; Soe, May Khin; E. Zainudin, Engku Nuraishah Huda; Afdzal Rasif, Muhammad Naif Hafizin; Nazri, Amirah Farhana (CR Subscription Agency, 2023)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder due to the body's ineffectiveness in responding to insulin. The prevalence of T2DM in Malaysia is increasing from year to year. Besides, diabetes is one of the Non-Communicable Diseases (NCDs) which are the leading cause of premature death due to its complications in Malaysia. Although pharmacological and surgical interventions are available in controlling T2DM, lifestyle modification provides an alternative way to reverse T2DM as the development of diabetes mellitus is highly related to lifestyle. The modifiable risk factors that lead to the causation of diabetes include being overweight or obese, a sedentary lifestyle, and being physically inactive. Losing weight through exercise and diet control is effective in delaying the progression of T2DM. It also improves cardiometabolic disease progression as an increase in insulin sensitivity. Diet and exercise are lifestyle interventions that can reduce weight. Thus, this systematic review aims to study the effectiveness of diet and exercise in reversing T2DM. Methods & Results: According to PRISMA guidelines, PubMed, Scopus, and Cochrane Library Database were used in this study for searching the related studies. 12 studies that investigated the effectiveness of diet and exercise in reversing T2DM were obtained and reviewed. The main search keywords were linked using the Boolean operators "AND" and "OR. Risk-of-bias assessment was done using JBI critical appraisal tools. Most of the studies reported a significant decline in BMI, fasting plasma glucose, and HbA1c values of intervention groups. Some studies reported T2DM remission and medication reduction after the intervention. Conclusion: Diet and exercise effectively reverse T2DM as significant weight loss was achieved. However, the long-term effect should be further evaluated as reviewed studies were limited in duration.